Vaginal Vault Closure Following Total Laparoscopic Hysterectomy: Laparoscopic versus Conventional Technique - A Comparative Study - Mukta Agarwal; Shivangni Sinha; Smita Singh; H. Haripriya; S Simran (Wolters Kluwer Medknow Publications, 2024)
Objectives: Vault closure is the final step to hysterectomy, protecting the abdominal cavity from the exterior environment. Thus, closure becomes crucial in preventing ascend of infection to the peritoneal cavity. Our study aims to compare vault closure between laparoscopic and vaginal routes, their operating time, and postoperative complications. Materials and Methods: The ambispective comparative study was done in a tertiary care teaching center from June 2016 to December 2022. Three hundred and forty-four patients were included in the study that underwent a total laparoscopic hysterectomy. Interventions - Patients who had laparoscopic vault closure were in Group 1 (N = 198) and those who had vaginal closure were in Group 2 (N = 146). The results were compared. It included age, body mass index of the patient, the indication of surgery, intraoperative blood loss, size of the uterus, time taken during vault closure, and postoperative complications. Results: The time taken by laparoscopic vault repair was significantly less than vaginal repair (19.7 ± 13.3 min vs. 30.1 ± 6.6 min, P < 0.001). There was postoperative vault infection (2.7%), vault hematoma (1.3%), and no vault prolapse seen in vaginal repair. The organisms isolated were mainly Pseudomonas aeruginosa, Escherichia coli, and Klebsiella. Conclusion: Laparoscopic vault closure has shown significantly improved results compared to vaginal route repair.